PREVENTING VIOLENT EXTREMISM DALAM PENDIDIKAN ANAK DAN SENI - Syaifudin Zuhri (LP2M IAIN Tulungagung, 2019)
A number of terrorist attacks and bombings involving children clearly demonstrates the fact that children are vulnerable to violent doctrines and ideologies. This article tries to formulate the Preventing Violent Extremism/PVE strategy into education, initially early education. The discussion aims also at unveiling the centrality of arts in the PVE project and the translation of PVE in Islamic-arts education for children. Examining some important related sources on PVE, education for children, and Islamic arts, the article argues arts education serves as an essential method to implant the principles of PVE and children’s participation in the PVE is inescapable. Principles of PVE, ranging from protecting from violence, exclusivism, radicalism, and extremism that culminate to terrorism, play roles in preventing children from ideologies that threaten their intellectual and emotional development.Keywords: Preventing Violent Extremism/PVE, Children Education, Islamic Art Beragam kasus terorisme dan bom bunuh diri yang melibatkan anak-anak memperlihatkan bahwa anak juga menjadi kelompok usia yang rentan terpapar doktrin dan ideologi kekerasan. Tulisan ini hendak mendiskusikan paradigm Preventing Violent Extremism/PVE dalam pendidikan, utamanya dalam pendidikan anak. Diskusi juga diarahkan pada kajian seni dengan menegaskan sentralitas seni dalam PVE dan bagaimana paradigm PVE dapat digunakan dalam pendidikan seni Islam bagi anak-anak. Menelusuri berbagai pustaka terkait PVE, pendidikan anak dan seni Islam, artikel ini berargumen bahwa seni menjadi saluran penting dalam program PVE dan keterlibatan anak-anak mutlak diperlukan. Dengan paradigm PVE, kekerasan, intoleransi, eksklusifisme, radikalisme, ekstrimisme, bahkan terorisme, dapat melindungi anak dari ideologi yang merusak pondasi intelektual dan emosional anak. Keywords: Preventing Violent Extremism/PVE, Pendidikan Anak, Seni Islam